IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN MATEMATIKA DI SDN 183/II SUMBER MULYA - Tresna Wati; Tri Wera Agrita; Nurlev Avana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research began with a problem where teachers experienced difficulties in preparing the flow of learning objectives, learning objectives, and difficulty modifying teaching modules to suit students' needs. The aim of this research is to describe the implementation of the independent curriculum in mathematics subjects and teachers' obstacles in planning, implementing and assessing independent curriculum learning in mathematics subjects. This research uses a descriptive qualitative method with a case study approach. The subjects of this research were class I, II, IV, and V teachers. The data collection techniques used were observation and interviews. Data analysis used in this research includes data reduction, data presentation, and drawing conclusions. Then the data is processed using triangulation of sources and methods. The results of this research are: (1) The implementation of the independent curriculum in mathematics subjects emphasizes character development and critical thinking skills. (2) The teacher's obstacle in planning learning is a lack of understanding of how to reduce learning outcomes to learning objectives. The teacher's obstacle in implementing learning is that students are lazy to count. The teacher's obstacle in learning assessment is the limited time used to complete the learning assessment.